2D/3D ZIF‐9/Mo15S19 S‐Scheme Heterojunction for Productive Photocatalytic Hydrogen Evolution. Issue 2 (17th November 2021) - Li, Junke; Li, Mei; Jin, Zhiliang
Abstract : Flower‐like Mo15 S19 nanoparticles are successfully attached on the surface of the lamellar cobalt‐based zeolite imidazole framework (ZIF‐9) according to the physical mixing process herein described. The existence of lamellar ZIF‐9 not only avoids the stacking of spherical flower‐like Mo15 S19 nanoparticles but also enhances the adsorbability of the ZIF‐9/Mo15 S19 system for Eosin‐Y (EY) molecules, which injects more vitality into the hydrogen production reaction. In addition, the lamellar ZIF‐9 can be freely stacked and form a regular rich wrinkle structure. Benefitting from this special structure, Mo15 S19 nanoparticles with spherical flower‐like shape can be adsorbed more firmly between the layers of ZIF‐9. This 2D/3D interlaced structure makes the system more stable, which also can improve the adsorption capacity of EY molecules. In addition, the construction of an S‐scheme heterojunction between ZIF‐9 and Mo15 S19 is another nonnegligible driving force for the enhanced photocatalytic performance in this system. The rational establishment of the S‐scheme heterojunction provides a more convenient transmission channel for the photogenerated charge. This work uses ZIF‐9 as the carrier of Mo15 S19 and promotes the catalytic performance of the composite ZIF‐9/Mo15 S19 by adjusting the evacuation of the spherical Mo15 S19 nanoparticles and constructing a heterojunction that can promote the flow ability of charges. Abstract : Via a simple physical mixing method, the composite of 2D/3D ZIF‐9/Mo15 S19 is successfully designed. ZIF‐9, as the lamellar framework, effectively inhibited the stacking of flower‐like Mo15 S19 nanoparticles. In addition, the S‐scheme heterojunction formed between ZIF‐9 and Mo15 S19 offers a more commodious electron transfer pathway and promotes the forward progress of the hydrogen evolution reaction.